The Failures of the United Nations Security Council's Resolutions in Addressing the Russia-Ukraine Conflict: Case Study of Resolution No. S/RES/2202 of 2015 - Suardi, Zulfikar; Nuzulian, Ully; Putri Olifiani, Laras (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2024)
This study aims to analyze the failure of Resolution No. S/RES/2202 of 2015, issued by the United Nations Security Council (UNSC), to address the conflict between Russia and Ukraine during 2014-2015. This research falls within the realm of qualitative research, utilizing a descriptive-analytical method and data collection through a literature review including books, journals, official documents, and relevant research. Johan Galtung's Conflict Transformation theory supports the research to analyze the failure of this resolution from the perspective of its inability to transform the conflict from internal to multi-dimension based on the variable of conflict transformation. The findings indicate that the resolution failed to build peace of the Russia-Ukraine conflict due to the non-implementation of the resolution's points. The UNSC should prepare legal enforcement measures through the UN General Assembly to restrict Russia's decision-making concerning the Ukrainian crisis.